2022
DOI: 10.1371/journal.pone.0274412
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, patterns, and attitude regarding dietary supplement use in Saudi Arabia: Data from 2019

Abstract: Dietary supplements are products containing dietary elements including vitamins, minerals, amino acids, herbs, or botanicals. They can aid consumers with low dietary intake and quality, as well as those with high demands, by boosting nutritious value. A cross-sectional study was conducted among adults living in Saudi Arabia aged between 18–60 years old using online self-administered questionnaire. Information regarding sociodemographic characteristics, use and type of dietary supplements, and attitude toward a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 28 publications
4
8
1
Order By: Relevance
“…Because of their high requirements for these compounds and their susceptibilities to their deficiencies, young children, pregnant women, and breastfeeding mothers are the populations that are most generally recognized as being prone to vitamin deficiencies [25]. The current study found that females consume more DS than males do (58%), which is approximately the same as the study that was carried out in Saudi Arabia (53.6%) [16]. However, the prevalence of use was found to be lower in Malaysia, at nearly 38% [26].…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Because of their high requirements for these compounds and their susceptibilities to their deficiencies, young children, pregnant women, and breastfeeding mothers are the populations that are most generally recognized as being prone to vitamin deficiencies [25]. The current study found that females consume more DS than males do (58%), which is approximately the same as the study that was carried out in Saudi Arabia (53.6%) [16]. However, the prevalence of use was found to be lower in Malaysia, at nearly 38% [26].…”
Section: Discussionsupporting
confidence: 68%
“…In the meantime, the vast majority of participants (73.3% of them) did not conduct any laboratory tests before or after intake of these supplements. This attitude was also documented among consumers of DS in Saudi Arabia (55% of them) [16]. When it came to the individuals who were taking vitamin D3, fewer than half of them (47.05%) carried out serum D3 evaluation tests both before and after they consumed this supplement.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations